How to Individuate the Powers of Knowledge and Opinion in Plato's Republic V - Brian David Prince (Revista de Filosofia Antiga, 2014)
At the end of Republic V Socrates argues that differences between knowledge and opinion justify rule by philosophers in his ideal city; within this argument he gives a theory of powers. The theory contains a logical gap: Socrates mentions two criteria by which he individuates powers, yet assumes in his argument that both criteria will speak with a single voice. I argue that these criteria are two ways of picking out a power’s manifestation—that is, the change a power is directed toward; I shall call this view the Identity Reading. Since they refer to a single phenomenon, the results of consulting both criteria cannot differ. The Identity Reading both solves the logical problem with the argument and sheds light four other features of the passage. This reading also provides support for what Gail Fine has called the “contents analysis” of a power’s relation to its “objects,” as opposed to the “objects analysis.”